Combination of Carotid Stenosis and Essential Thrombocythemia in a Male Patient with Homozygous JAK2 Mutation: Case Report - Yokuş, Osman; Gökalp, Süleyman Sırrı; Balçık, Özlem Şahin; Albayrak, Murat; Ersaydı, Mehmet (Fırat University, 2011)
A forty-six year-old male patient presented with complaints of syncopal attacks that last for 1-3 seconds, headache, and burning and redness on toes for the last two months. In his laboratory examination, platelet count was 1500x109/L, leukocyte count was 17x109/L, and hematocrit level was 55%. Janus Kinase 2 V617F (JAK2) homozygous mutation was detected with polymerase chain reaction (PCR). The patient was diagnosed with essential thrombocythemia (ET). In the evaluation of syncopal attacks, stenosis with a length of 2.5 cm, which constricted the right carotid artery lumen at a ratio of 65%, was detected. In this case report, the diagnosis and treatment modalities were discussed in a patient diagnosed with ET who has JAK2 mutation and carotis artery stenosis.

Kırk altı yaşında erkek hasta; son iki aydır, 1-3 saniye süren senkop atakları, baş ağrısı, ayak parmaklarında yanma ve kızarıklık şikayetleri ile başvurdu. Laboratuvar incelemesinde; trombosit sayısı 1500x109/L, lökosit sayısı 17x109/L, hematokrit düzeyi %55 idi. Polimeraz zincir reaksiyonu (PCR) ile Janus Kinaz 2 V617F (JAK2) homozigot mutasyonu tespit edildi. Hastaya esansiyel trombositemi (ET) tanısı kondu. Senkop ataklarına yönelik değerlendirmede sağ karotis arter lümenini %65 oranında daraltan, 2.5 cm uzunlukta stenoz saptandı. Bu olgu sunumunda; homozigot JAK2 mutasyonu taşıyan ve karotis arter stenozu saptanan ET tanılı olguda tanı ve tedavi yaklaşımları tartışılmıştır.
Homozigot JAK2 Mutasyonlu Erkek Hastada Karotis Stenozu ve Esansiyel Trombositemi Birlikteliği: Olgu Sunumu